Buenas prácticas en la educación del cuerpo en la escuela inicial y básica - Lescano, A. (Comp.) (Cuerpo, Educación y Sociedad, 2018)
With the objective of tracking good educational practices, the Brazilian universities of Santa Catarina and Paraná together with the Universidad Nacional de La Plata joined in a research based on three school institutions' ethnographies.